A interação como instrumento de aprendizagem na educação infantil: um estudo de caso em uma escola sociointeracionista no centro de Belém/PA - MONTEIRO, Tamires Shirlene dos Santos (2023)
A child is born inserted in a certain society and at a historic time, to have relations with the environment where he lives, he discovers a world that contributes to human development through interactive experiences. These interactions allow the learning and the construction of the identity of the child as a social being and history that is part of a culture, a fact that confirms the importance of discussing how the social interactionism of Vygostsky contributes to Early Childhood Education. In this sense, a qualitative research with bibliographic research and case study was performed. The analyzes made it possible to understand the learning process of children from the socio-historical theory, and to identify the characteristics of a sociointeractionist school through a case study in a school in the center of Belém, as well as to describe the pedagogical actions of sociointeractionist teachers in Children's learning process in early childhood education from the case study. Finally, it is concluded that the school based on Vygotsky's sociointeractionism allows for a more complete formation of the child, allowing him to become and build himself as a person beyond the school walls, confirming himself as a subject in the social space. where you live.